Alternative fuels for marine applications - Kolwzan, K., Polish Register of Shipping, Gdansk (Poland). Dept. of Machinery and Equipment; Narewski, M., Polish Register of Shipping, Gdansk (Poland). Dept. of Machinery and Equipment (Latvijas k̦īmijas žurnāls, 2012)
This paper outlines the growing number of shipboard applications of new, alternative fuels such as: low sulphur fuels, gas fuels and biofuels in the global maritime transport. Advantages of the new fuels, their functional basis, is limited to applicability and current development issues have been shown, including the analysis of cost predictions. All types of marine fuels are subject of certain quality, documentation and survey procedures. EU policy is an example where international standards are being transferred to national level, and where marine standards result in mirror action in inland waterway air pollution prevention measures. Lai samazinātu siltumnīcas gāzu izmešus, kuģniecības industrija (kuģu īpašnieki, kuģu būvētāji, klasificēšanas sabiedrības) meklē jaunu, alternatīvu degvielu avotus. Tie var būt biodegviela un sašķidrināta dabas gāze.